Genomic content and new insights on the origin of the B chromosome of the cichlid fish Astatotilapia latifasciata - Fantinatti, Bruno E. A. [UNESP]; Mazzuchelli, Juliana [UNESP]; Valente, Guilherme T. [UNESP]; Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Martins, Cesar [UNESP] (Springer, 2011)
B chromosomes are additional chromosomes widely studied in a diversity of eukaryotic groups, including fungi, plants and animals, but their origin, evolution and possible functions are not clearly understood. To further understand the genomic content and the evolutionary history of B chromosomes, classical and molecular cytogenetic analyses were conducted in the cichlid fish Astatotilapia latifasciata, which harbor 1-2 B chromosomes. Through cytogenetic mapping of several probes, including transposable elements, rRNA genes, a repeated DNA genomic fraction (C (0) t - 1 DNA), whole genome probes (comparative genomic hybridization), and BAC clones from Oreochromis niloticus, we found similarities between the B chromosome and the 1st chromosome pair and chromosomes harboring rRNA genes. Based on the cytogenetic mapping data, we suggest the B chromosome may have evolved from a small chromosomal fragment followed by the invasion of the proto-B chromosome by several repeated DNA families.
Keywords: Cytogenetics; Evolution; Genome; Repeated DNA; Supernumerary chromosome